2006
DOI: 10.1097/01.wnr.0000220128.01597.e0
|View full text |Cite
|
Sign up to set email alerts
|

Can stroke patients walk after complete lateral corticospinal tract injury of the affected hemisphere?

Abstract: The lateral corticospinal tract is the major motor pathway in humans. The role of this tract on walking, however, is uncertain. The development of di¡usion tensor tractography enables corticospinal tract status to be visualized at the subcortical level. In the present study, we undertook to demonstrate that some stroke patients can walk despite complete lateral corticospinal tract injury. Ten stroke patients who were able to walk with evidence of complete unilateral lateral corticospinal tract injury, as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…17 The evolution of the corticospinal tract (CST) in mammals is associated with the acquisition of motor skills. Several studies show that people affected by stroke could walk even after extensive damage of the lateral CST, [18][19][20] although the upper-limb motor function remains severely 1 Scientific Institute Vita-Salute University San Raffaele, Milan, Italy impaired. 20,21 However, CST is considered essential for skilled gait by modulating the walking pattern in response to environmental influences.…”
Section: Neural Control Of Lower-limb Motor Function and Normal Walkingmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The evolution of the corticospinal tract (CST) in mammals is associated with the acquisition of motor skills. Several studies show that people affected by stroke could walk even after extensive damage of the lateral CST, [18][19][20] although the upper-limb motor function remains severely 1 Scientific Institute Vita-Salute University San Raffaele, Milan, Italy impaired. 20,21 However, CST is considered essential for skilled gait by modulating the walking pattern in response to environmental influences.…”
Section: Neural Control Of Lower-limb Motor Function and Normal Walkingmentioning
confidence: 99%
“…Several studies show that people affected by stroke could walk even after extensive damage of the lateral CST, [18][19][20] although the upper-limb motor function remains severely 1 Scientific Institute Vita-Salute University San Raffaele, Milan, Italy impaired. 20,21 However, CST is considered essential for skilled gait by modulating the walking pattern in response to environmental influences. [19][20][21][22] Fine control of walking involves several brain regions, including the sensorimotor cortex, supplementary motor area (SMA), cerebellum, and brainstem.…”
Section: Neural Control Of Lower-limb Motor Function and Normal Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The descending motor pathways are classified according to the corticospinal tract (CST, pyramidal tract) and non-CST (extrapyramidal tract). 6,7 A number of studies have reported on stroke patients who were unable to perform fine motor activities of the hands after complete injury of the lateral CST; [8][9][10][11][12] in contrast, recent studies have demonstrated that stroke patients were able to walk even after complete injury of the lateral CST, suggesting that walking is not as strongly associated with the lateral CST as hand function. 3,9,[13][14][15] Greater involvement of non-CSTs in walking ability has been suggested.…”
mentioning
confidence: 99%
“…6,7 A number of studies have reported on stroke patients who were unable to perform fine motor activities of the hands after complete injury of the lateral CST; [8][9][10][11][12] in contrast, recent studies have demonstrated that stroke patients were able to walk even after complete injury of the lateral CST, suggesting that walking is not as strongly associated with the lateral CST as hand function. 3,9,[13][14][15] Greater involvement of non-CSTs in walking ability has been suggested. 9,14,15 In particular, the corticoreticulospinal tract, consisting of the corticoreticular pathway (CRP) and the reticulospinal tract, is known to be an important neural tract for walking ability [14][15][16] because it mainly mediates proximal and axial muscles; consequently, it is known to have a major role in relation to walking ability.…”
mentioning
confidence: 99%